2018
DOI: 10.2147/ndt.s166322
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect effects of α-synuclein on microtubule stability in the pathogenesis of Parkinson’s disease

Abstract: Despite decades of research, the mechanism of Parkinson’s disease pathogenesis remains unclear. Studies have focused heavily on the protein α-synuclein, which is the primary component of Lewy bodies, the pathologic inclusions that are the hallmark of Parkinson’s on the cellular level. While the roles of α-synuclein in causing mitochondrial dysfunction and disruptions to the proteasomal system have been well documented, recently, its role in effecting microtubule dynamics has been investigated as a potential so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…37 The phosphorylation of Tau reduces its affinity for microtubules and accumulation in the brain and causing related Tauopathies, 17 and also impact on microtubule binding and induces microtubule instability. 4 Although p-Tau links to the pathogenesis of AD and other Tauopathies, recent studies have revealed that p-Tau has a relationship with PD. 46 MAPT (encoded Tau protein) gene mutation in humans increases the risk of PD, and Tau aggregation and filaments have been observed in familial PD.…”
Section: Introductionmentioning
confidence: 99%
“…37 The phosphorylation of Tau reduces its affinity for microtubules and accumulation in the brain and causing related Tauopathies, 17 and also impact on microtubule binding and induces microtubule instability. 4 Although p-Tau links to the pathogenesis of AD and other Tauopathies, recent studies have revealed that p-Tau has a relationship with PD. 46 MAPT (encoded Tau protein) gene mutation in humans increases the risk of PD, and Tau aggregation and filaments have been observed in familial PD.…”
Section: Introductionmentioning
confidence: 99%
“…The current revision summarizes the studies supporting the link between αSyn and the actin cytoskeleton. This is an important topic as while the interplay between αSyn and the microtubules was recently reviewed (Carnwath et al, 2018;Calogero et al, 2019), the link αSyn-actin was less explored. Considering the αSyn structural features responsible for the interaction with cytoskeleton components, it was described that αSyn is a functional microtubule-associated protein with its C-terminal region suggested to be responsible for the interaction with microtubules (Alim et al, 2004;Cartelli et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…By directly or indirectly binding tubulin, these proteins have been reported to modulate MT stability and function [ 268 , 269 , 270 , 271 , 272 ].…”
Section: Microtubule Dysfunction and Neurodegenerationmentioning
confidence: 99%
“…α-Syn is a small, soluble unfolded protein that localizes predominantly to presynaptic terminals of neurons [ 286 ]. Although little is known about the mechanisms through which α-Syn acts in PD, different studies have recently proposed that this protein may act as a functional MAP by directly binding MTs [ 272 , 287 ] and regulating their stability. However, the effect of this interaction has been quite controversial, since different studies have reported that α-Syn, promotes MT stabilization, while others suggested the opposite effect [ 287 , 288 ].…”
Section: Microtubule Dysfunction and Neurodegenerationmentioning
confidence: 99%